2014
DOI: 10.5152/tjg.2014.2531
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver damage and anorexia nervosa: A case report

Abstract: Anorexia nervosa is an eating disorder predominantly affecting young women and characterized by an intense fear of gaining weight and becoming fat. Liver injury with mild elevation of hepatic enzymes is a frequent complication, and steatosis of the liver is thought to be the major underlying pathology. However, acute hepatic failure with transaminase levels over 1000 u/L is a very rare complication, and the precise mechanism of the liver injury is still unclear. We report a case of a 35-year-old woman with a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…Several studies reported elevations in alanine transaminase (ALT) greater than aspartate transaminase (AST) and others have shown the reverse . Similarly a number of studies noted elevated alkaline phosphatase (ALP) and bilirubin while others have not. Several studies noted the patients developed severe hypoglycemia, all of which then required transfer to the ICU at some point during their treatment, suggesting that significant hypoglycemia may be a marker for imminent severe liver failure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies reported elevations in alanine transaminase (ALT) greater than aspartate transaminase (AST) and others have shown the reverse . Similarly a number of studies noted elevated alkaline phosphatase (ALP) and bilirubin while others have not. Several studies noted the patients developed severe hypoglycemia, all of which then required transfer to the ICU at some point during their treatment, suggesting that significant hypoglycemia may be a marker for imminent severe liver failure.…”
Section: Resultsmentioning
confidence: 99%
“…104,113,120 In the vast majority of patients with AN and elevated transaminases, the only treatment necessary is gradual refeeding and hydration, which leads to complete normalization of liver enzymes over time. 100,101,105,106,110,113,114 The time course to peak transaminase levels during refeeding appears to be 2 to 5 days after which transaminase level then start to recede and normalize between Day 20 and Day 40 of the refeeding process. 99,106,110 Published studies have not presented a consistent pattern with regards to the elevation of liver enzymes.…”
Section: Liver Abnormalitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment is hydration, correction of electrolytes and fluid imbalance, and gradual nutritional support to prevent refeeding syndrome [8]. The patient exhibits elevated serum transaminases, elevated alkaline phosphatase, and prolonged prothrombin time, which collectively are suggestive of acute liver failure.…”
Section: Discussionmentioning
confidence: 99%